Breast cancer screening a literature review - Alsammak, Mai; Khattabi, Marwa (International Journal Of Community Medicine And Public Health, 2023)
This article is looking at literature on breast cancer screening. Being the most common cancer worldwide and a leading cause of death, screening asymptotic women leads to early detection hence early treatment and with advances in treatments, breast cancer has better survival outcomes.